Correlation of heart failure severity and N-terminal pro-brain natriuretic peptide level in children - Yasmien Mahrani; Ria Nova; Masagus Irsan Saleh; Kemas Yakub Rahadianto (Paediatrica Indonesiana, 2016)
Background  Heart failure affects morbidity and mortality in children with heart disease. There is no single, specific test to diagnose heart failure. The modified Ross Reithmann scoring system has been used to classify heart failure severity, but it is limited due to its subjectivity. The N-terminal pro-brain natriuretic peptide (NT-proBNP) is secreted by the ventricles during heart failure. It has been suggested as a possible marker for diagnosing heart failure.Objective To investigate the correlation between heart failure severity and plasma NT-proBNP concentration in children aged one month to 14 years.Methods A cross-sectional study was performed in the Pediatrics Department of Mohammad Hoesin Hospital from July to September 2015 on children with congestive heart failure, aged one month to 14 years. Heart failure severity was assesed using the modified Ross Reithmann scoring system. Plasma NT-proBNP measurements were done in all subjects. Statistical analysis was done by Spearman’s test.Results  Subjects’ median plasma NT-proBNP concentration was 1,703 pg/mL (range 310-9,000 pg/mL). The NT-proBNP level and severity of heart failure had a significant, positive correlation (r=0.87; P<0.001). The NT-proBNP minimum levels in subjects with mild, moderate and severe heart failure were 310 pg/mL, 1,251 pg/mL, and 2,610 pg/mL, respectively.Conclusion Plasma NT-proBNP level has a significant, positive correlation with the severity of heart failure in children. As such, NT-proBNP level may be useful as a biochemical marker for the diagnosis and grading of the severity of heart failure in children.